THE SCOPE OF CONTEMPORARY MODERN ECONOMICS: A LITERATURE REVIEW ON THE INTERACTION BETWEEN PRODUCTION, CONSUMPTION, INSTITUTIONAL STRUCTURE, TECHNOLOGY, GLOBAL FINANCE, AND SOCIAL–ENVIRONMENTAL ISSUES - Farida Akbarina; Ahmad Rizani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study discusses the scope of the contemporary modern economy through a literature review that examines the interaction between production, consumption, institutional structure, technology, global finance, and social-environmental issues. The results of the study show that the contemporary modern economy can only be understood holistically through a multidisciplinary approach that integrates economic, social, and environmental aspects. These findings provide a conceptual basis for the formulation of policies that are more inclusive, sustainable, and responsive to global dynamics.